Endotracheal suction interventions in mechanically ventilated children: An integrative review to inform evidence-based practice. Issue 1 (January 2021) - Schults, Jessica A.; Mitchell, Marion L.; Cooke, Marie; Long, Debbie A.; Ferguson, Alexandra; Morrow, Brenda
Abstract: Objective: The objective of this study was to review and critically appraise the evidence for paediatric endotracheal suction interventions. Data sources: A systematic search for studies was undertaken in the electronic databases CENTRAL, Medline, EMBASE, and EBSCO CINAHL from 2003. Study selection: Included studies assessed suction interventions in children (≤18 ys old) receiving mechanical ventilation. The primary outcome was defined a priori as duration of mechanical ventilation. Secondary outcomes included adverse events and measures of gas exchange and lung mechanics. Data extraction: Data extraction were performed independently by two reviewers. Study methodological quality was assessed using Cochrane's risk of bias tool for randomised trials or the Newcastle–Ottawa Scale for observational studies. Overall assessment of the certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluations criteria. Results: Overall 17 studies involving 1618 children and more than 21, 834 suction episodes were included in the review. The most common intervention theme was suction system (five studies; 29%). All included trials were at unclear or high risk of performance bias due to the inability to blind interventionists. Current evidence suggests that closed suction may maintain arterial saturations, normal saline leads to significant transient desaturation, and lung recruitment applied after suction offers short-term oxygenation benefit. Limitations: Lack of randomised controlled trials, inconsistencies in populations and interventions across studies, and imprecision and risk of bias in included studies precluded data pooling to provide an estimate of interventions effect. Conclusions: Based on the results of this integrative review, there is insufficient high-quality evidence to guide practice around suction interventions in mechanically ventilated children.